Penatalaksanaan Fisioterapi pada Kasus Post Operasi Total Knee Replacement Et Causa Osteoarthritis Di Rumah Sakit Orthopedi DR. Soeharso Surakarta - Nurhafizh, Muhammad Isnan; , Wijianto SSt. FT. M. OR (2016)
Background : Total knee replacement is treatment to decrease pain and recovery functional activity to patient with osteoarthritis it can't cover by physical therapy. Pain and decrease of funtional activity have felt in patient after surgery. Exercise therapy can help this problems. Result : After doing exercise therapy about five times the results of the assessment of hold pain T1: 4 to T5: 3, pressure pain T1: 7 to T5: 5 and motion pain T1: 8 to T5: 5. Difference value oedem at knee dextra and sinistra with measurment at 5 cm to proximal T1: 7 cm to T5: 5 cm. 10 cm to proximal T1: 6 cm to T5: 4cm. 5 cm to distal T1: 5 cm to T5: 3 cm. 10 cm to distal T1: 3 cm to T5: 2 cm. Value oedem at ankle dextra and sinistra T1 : 70 cm to T5: 67 cm. Increase muscle strenght on extensor hip T1: 2- to T5: 2, abductor hip T1:2- to T5: 3-, adductor hip T1: 2- to T5: 2, eksorotator hip T1: 2- to T5: 2, endorotator hip T1: 2- to T5: 2. Fleksor knee T1: 2- to T5: 3-. ekstensor knee T1: 2- to T5: 2. Increase range of motion hip T1: S: 0°-0°-90° to T5: 10°-0°-100°, T1: F: 10°-0°-10° to T5 : 15°-0°- 10°, T1: R: 20°-0°-20° to T5: 25°-0°-20°. Range of motion knee T1: S: 0°-5°-25° to T5: 0°-0°-30°. Range of motion ankle T1: S: 10°-0°-40° to T5: 15°-0°-40°. Increase of funtional activity T1: 89% to T5 64%. Conclusion : Exercise therapy can decrease pain and oedema, Increase muscle strenght, increase range of motion and functional activity. Keyword : Total Knee Replacement, osteoarthritis, Exercise Therapy, ROM exercise, gait exercise, strenghthening, hold rileks.